System of International Legal Standards for Ensuring Human Rights and Freedoms at the Pre-trial Investigation Stage - S. M. Danylo (Bulletin of Kharkiv National University of Internal Affairs, 2025)
It is emphasised that the system of international legal standards for ensuring human rights and freedoms at the pre-trial investigation stage is fundamental to any democratic state governed by the rule of law. It has been established that in conditions of martial law and against the backdrop of contemporary challenges to justice, these standards take on particular significance and require specific interpretation and application. A comprehensive analysis and systematisation of international legal standards for ensuring human rights and freedoms at the stage of pre-trial investigation was carried out. The essence and characteristics of the system of international legal standards for ensuring human rights and freedoms in the context of modern approaches to criminal proceedings have been examined. It has been proposed that the system of international legal standards for ensuring human rights and freedoms at the stage of pre-trial investigation should be understood as an integrated, dynamic set of mandatory and recommended norms of international law, which, as recognised by Ukraine and implemented in its criminal procedural legislation, establish minimum requirements for the activities of pre-trial investigation bodies and determine the legal status of a person in criminal proceedings, ensuring comprehensive protection of their rights and freedoms, in particular in conditions of martial law and taking into account the practice of international judicial institutions. It is emphasised that the system of international legal standards for ensuring human rights and freedoms at the stage of pre-trial investigation should be formed taking into account a comprehensive approach and consider both general principles and specific guarantees relating to various aspects of the activities of pre-trial investigation bodies and the legal status of participants in the proceedings. It is emphasised that the system of international legal standards for ensuring human rights and freedoms at the stage of pre-trial investigation should be flexible enough to adapt to the conditions of special legal regimes and remain steadfast in ensuring fundamental human rights. Key international legal standards governing the activities of pre-trial investigation bodies have been identified and systematised, taking into account the specifics of martial law and contemporary challenges to justice: standards defining the general principles of pre-trial investigation; standards regulating procedural actions; standards of evidence during pre-trial investigation; standards regulating the participation of certain categories of persons; standards of effective legal protection and control.